氷雪性緑藻Chloromonas属の日本産１未記載種 - 松崎, 令; 野崎, 久義; 竹内, 望; 原, 慶明; 河, 地正伸; Ryo, Matsuzaki; Hisayoshi, Nozaki; Nozomu, Takeuchi; Yoshiaki, Hara; Masanobu, Kawachi (2017)
第8回極域科学シンポジウム/個別セッション：[OB] 極域生物圏 12月5日（火）国立極地研究所 1階交流アトリウム The Eighth Symposium on Polar Science/Ordinary sessions: [OB] Polar Biology Tue. 5 Dec./Entrance Hall (1st floor), National Institute of Polar Research conference object